2013
DOI: 10.1089/eco.2012.0084
|View full text |Cite
|
Sign up to set email alerts
|

“Doing” Gardening and “Being” at the Allotment Site: Exploring the Benefits of Allotment Gardening for Stress Reduction and Healthy Aging

Abstract: The purpose of this study was to investigate the benefits to health and well-being of allotment gardening (in Wales, UK) in a communitydwelling older adult sample, with a particular emphasis on stress recovery. Semi-structured interviews were used to explore allotment gardener participants' personal beliefs and ideas of the benefits of their allotment gardening activity. The transcribed interviews were examined using thematic analysis. It was assumed that through the discussion of positive aspects of allotment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 39 publications
3
80
0
Order By: Relevance
“…Beyond improving access to more nutritious food, urban agriculture can also improve the physical health of growers through the exertion involved in cultivation and harvesting, and mental health can be maintained through an improved connection to nature and increased community cohesion (Wakefield et al 2007;Clatworthy et al 2013;Hawkins et al 2013). For example, it has been found in the Netherlands that allotment holders are healthier than their neighbours without allotments, although this was only significant for those over the age of 62 (van den Berg et al 2010).There is also evidence of more diffuse benefits of urban farming beyond those that grow and consume the food, since the simple presence of greenspace in cities is also positively associated with human health (Groenewegen et al 2012).…”
Section: Contributions To Sustainable Development Goal 3 (Health)mentioning
confidence: 99%
“…Beyond improving access to more nutritious food, urban agriculture can also improve the physical health of growers through the exertion involved in cultivation and harvesting, and mental health can be maintained through an improved connection to nature and increased community cohesion (Wakefield et al 2007;Clatworthy et al 2013;Hawkins et al 2013). For example, it has been found in the Netherlands that allotment holders are healthier than their neighbours without allotments, although this was only significant for those over the age of 62 (van den Berg et al 2010).There is also evidence of more diffuse benefits of urban farming beyond those that grow and consume the food, since the simple presence of greenspace in cities is also positively associated with human health (Groenewegen et al 2012).…”
Section: Contributions To Sustainable Development Goal 3 (Health)mentioning
confidence: 99%
“…Recently there has been a renewed interest in allotments, as people are increasingly opting for greener lifestyles (Wiltshire & Burn, 2008). A number of health and wellbeing benefits of allotment gardening have been claimed, including stress reduction, a sense of accomplishment and enjoyment (Hawkins, Mercer, Thirlaway & Clayton, 2013), and increased physical activity, relaxation and community cohesion (Hope & Ellis, 2009). However, despite the 3 growing interest in the wellbeing benefits of allotment gardening, research in this area is still in early stages.…”
Section: Allotment Gardening and Wellbeingmentioning
confidence: 99%
“…Fathers have reported developing stronger relationships with their children through spending time together on the allotment (Mason & Conneeley, 2012). Moreover, other research has indicated that the activity of gardening and 'being' in allotments both contribute to a sense of wellbeing (Hawkins et al, 2013). …”
mentioning
confidence: 99%
“…There are many reasons why individuals may choose gardening as a leisure activity. Previous research has shown that close contact with nature has many psychological benefits, including increased attentional functioning (Kaplan, 1995), stress reduction (Hawkins, Mercer, Thirlaway, & Clayton, 2013), and opportunities for socialization while gardening at communal sites (Kaplan, 1973). However, the benefits of gardening are not limited to the psychological, and studies have shown that those who have close contact with nature experience better overall health (Crouch et al, 2000;Kortright & Wakefield, 2011;Wakefield, Yeudall, Taron, Reynolds, & Skinner, 2007), including reductions in allcause mortality (Mitchell & Popham, 2008).…”
Section: Introductionmentioning
confidence: 99%